Odpowiedź :
1.
[tex]a)\\f(x) = 3(x+2)^2-6\\f(x) = 3(x^2+4x+4)-6\\f(x)=3x^2+12x+12-6\\f(x)=3x^2+12x+6\\\\\\b) \\f(x) = -2(x-3)^2+18\\f(x)=-2(x^2-6x+9)+18\\f(x)=-2x^2+12x-18+18\\f(x)=-2x^2+12x\\\\c) \\f(x) = (x+5)^2-24\\f(x)=x^2+10x+25-24\\f(x)=x^2+10x+1\\\\d) \\f(x) = \frac12(x-2)^2-10\\f(x)=\frac12(x^2-4x+4)-10\\f(x)=\frac12x^2-2x+2-10\\f(x)=\frac12x^2-2x-8[/tex]
2.
a)
[tex]f(x) = x^2-2x+3\\p=\frac{-b}{2a} => \frac{-(-2)}{2*1}=\frac22=1\\q=\frac{-\Delta}{4a} => \frac{-((-2)^2-4*1*3)}{4*1}=\frac{-(4-12)}{4}=\frac{8}4=2\\\\f(x)=a(x-p)^2+q\\[/tex]
b)
[tex]f(x) = 2x^2+8x+3\\p=\frac{-8}{2*2}=\frac{-8}4=-2\\q=\frac{-(8^2-4*2*3)}{4*2}=\frac{-(64-24)}8=\frac{-40}8=-5\\f(x)=2(x+2)^2-5[/tex]
c)
[tex]f(x) = -2x^2+16x-22\\p=\frac{-16}{-2*2}=\frac{-16}{-4}=4\\q=\frac{-(16^2-4*(-2)*(-22))}{-2*4}=\frac{-(256-176)}{-8}=\frac{-80}{-8}=10\\f(x)=-2(x-4)^2+10\\[/tex]
d)
[tex]f(x) = -\frac14x^2-2x\\p=\frac{2}{2*(-\frac14)}=\frac2{-\frac12}=2:(-\frac12)=2*(-2)=-4\\q=\frac{-((-2)^2-4*(-\frac14)*0)}{4*(-\frac14)}=\frac{-4}{-1}=4\\f(x)=-\frac14(x+4)^2+4\\[/tex]
3.
a)
[tex]f(x)=-x^2+5x-7\\\Delta=5^2-4*(-1)*(-7)\\\Delta=25+4*(-7)\\\Delta=25-28\\\Delta=-4[/tex]
b)
[tex]f(x)=2x^2-4\\\Delta=0^2-4*2*(-4)\\\Delta=0-8*(-4)\\\Delta=0+32\\\Delta=32[/tex]
c)
[tex]f(x) = 3x^2-2x+1\\\Delta=(-2)^2-4*3*1\\\Delta=4-12\\\Delta=-8[/tex]
d)
[tex]f(x)=-\frac12x^2+6x\\\Delta=6^2-4*(-\frac12)*0\\\Delta=36-0\\\Delta=36[/tex]
4.
a)
[tex]f(x)=2x^2+bx-1\\l : x=-3\\x = p\\p=\frac{-b}{2a}\\-3=\frac{-b}{2*2}\\-3=\frac{-b}4 /*4\\-12=-b\\b=12\\[/tex]
b)
[tex]f(x)=x^2+bx+6\\l: x=5\\x = p\\p = \frac{-b}{2a}\\5=\frac{-b}{2} /*2\\10=-b /*(-1)\\b=-10[/tex]